ANALYSIS OF TOPOGRAPHICAL CONTRIBUTION OF FLOODING IN OWERRI URBAN IMO STATE USING GIS AND REMOTE SENSING TECHNIQUES - Ibeabuchi Iro, Sylvanus; Chibuike Njoku, Francis (African Journal of Social and Behavioural Sciences, 2024)
Flooding poses a significant environmental challenge in Owerri Urban, Imo State, Nigeria, exacerbated by rapid urbanization, inadequate infrastructure, and heavy rainfall. This study examines the topographical contributions to flooding in Owerri using Geographic Information Systems (GIS) and remote sensing techniques. By analysing Digital Elevation Models (DEM), slope gradients, hill shade, aspect, and contour maps, the study identifies key areas prone to flooding. The findings reveal that flat or gently sloping areas, particularly those with a slope gradient of 0° to 40°, are most susceptible to run-off accumulation and flood events. The study further highlights the role of flat or gently sloping areas (0° to 40° slope gradient) in contributing to flood risk.", especially at the bases of slopes, where runoff from higher elevations accumulates. These insights underscore the critical role of topography in flood risk assessment and provide a foundation for developing targeted flood mitigation strategies. The study recommends the construction of a comprehensive drainage network, the integration of flood risk maps into urban planning, and the enforcement of land use regulations to reduce flooding in Owerri Urban. The use of GIS and remote sensing in this analysis demonstrates their effectiveness in enhancing urban resilience to environmental hazards.